LEVERAGING STAKEHOLDER ENGAGEMENT FOR ENHANCED HIGHER EDUCATION COMPETITIVENESS IN ARMENIA (Education in the 21st Century, 2023)
Armenia is facing the challenge of ensuring the competitiveness of its higher education institutions (HEIs) in the rapidly evolving global landscape of higher education. With the rising demands for competitive human capital and the development of knowledge-based economies, the HEIs of the Republic of Armenia (RA) need to be agile and strategic in their decision-making processes and in employing respective mechanisms to meet the demands of the market and global landscape of higher education. In this context, stakeholder engagement should emerge as a powerful tool for driving competitiveness through ethical and efficient decision making in higher education strategic management in Armenia, for it ensures the increase of stakeholders' interest, fiduciary responsibilities, and commitment towards HEIs.
Keywords: strategic management; stakeholder participation; competitiveness of higher education; fiduciary functions of university decision-making bodies; global higher education